2013
DOI: 10.4161/epi.26546
|View full text |Cite
|
Sign up to set email alerts
|

A key role for EZH2 in epigenetic silencing of HOX genes in mantle cell lymphoma

Abstract: The chromatin modifier EZh2 is overexpressed and associated with inferior outcome in mantle cell lymphoma (McL). Recently, we demonstrated preferential DNa methylation of hOX genes in McL compared with chronic lymphocytic leukemia (cLL), despite these genes not being expressed in either entity. since EZh2 has been shown to regulate hOX gene expression, to gain further insight into its possible role in differential silencing of hOX genes in McL vs. cLL, we performed detailed epigenetic characterization using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…The latter, the PRC2-complex catalytic subunit, is the target of recurrent somatic mutations in lymphomas including SMZL, 6,34 and its pharmacologic inhibition represents one of the new actively explored therapeutic modalities. [35][36][37] Transcriptional silencing driven by CpG methylation is strictly connected with the activity of the PRC2-complex, which represses expression of differentiation genes through tri-methylation of lysine 27 of histone H3 (H3K27me3). 11 Importantly, when compared with nontumoral splenic tissue, both Low-M and High-M SMZL cases presented high methylation and downregulation of genes harboring H3K27me3 and H3K4me3 methylation marks, and the phenomenon was more significant for the High-M cases.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, the PRC2-complex catalytic subunit, is the target of recurrent somatic mutations in lymphomas including SMZL, 6,34 and its pharmacologic inhibition represents one of the new actively explored therapeutic modalities. [35][36][37] Transcriptional silencing driven by CpG methylation is strictly connected with the activity of the PRC2-complex, which represses expression of differentiation genes through tri-methylation of lysine 27 of histone H3 (H3K27me3). 11 Importantly, when compared with nontumoral splenic tissue, both Low-M and High-M SMZL cases presented high methylation and downregulation of genes harboring H3K27me3 and H3K4me3 methylation marks, and the phenomenon was more significant for the High-M cases.…”
Section: Discussionmentioning
confidence: 99%
“…Many sgRNAs may be prone to high failure rates, thus trial-and-error to achieve gene editing may be impractical. Methods for opening closed chromatin, such as transcription activators 29 , and inhibitors of heterochromatin proteins 30,31 , might enhance Cas9 editing efficiency. We observed that treating cells with siRNA against the silencing protein SuZ12 led to full recovery of editing efficiency, comparable to the basal expression state ( Figure 6).…”
Section: Cc-by-nc-mentioning
confidence: 99%
“…The promising power of RNAi for therapeutic purposes and gives new hope that a potent tool for the reversion of an oncogenic phenotype is now in our hands (Humphries et al, 2013). BCR/ABL protein is considered relatively stable to the antisense attack (half-life, 48 hours), and it is difficult to influence its level by a single application of anti-BCR/ABL substances (Kanduri et al, 2013). The effects of siRNAs seem to be transient and have a poor influence on cell viability despite the well expressed, siRNA-mediated reduction of BCR/ABL mRNAs and oncoproteins described in the current study (Almalik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%